Listening Learning of Indonesian for Speakers of Other Languages (BIPA) for Academic Purposes - Widi Astuti; Nurhadi Bewe (STKIP Singkawang, 2020)
Indonesian is now increasingly in demand to be studied by foreign speakers for various purposes. One of the purposes for foreign speakers to learn Indonesian is related to academic purpose. BIPA learning with academic purposes has different characteristics from BIPA learning in general. This study aims to describe listening learning in the BIPA program for academic purposes at Universitas Negeri Yogyakarta based on the aspects of learning preparation and implementation which includes learning activities, learning materials, learning media, learning assessments, problems, and solutions in learning. The subject of this research is a lecturer of listening skills in the BIPA program for academic purposes in the class of Yunnan Minzu University, China. This research used a descriptive qualitative method. Data collection was carried out by observation, interviews, and document study. Data analysis techniques include data reduction, data display, and verification. The validity of the research data was carried out using triangulation methods. The results showed that the learning preparation was carried out by making a syllabus and developing learning materials. Listening learning activities were carried out through pre-listening, while-listening, and post-listening activities. Listening learning materials tailored the academic needs and adjusted to the speaking skills that learners will learn. The learning media used are handouts, audio, and video that were connected from the laptop to speakers and/or projectors. Learning assessment was carried out at the middle of the semester and the end of the semester. Problems encountered in learning include a technical problem and a non-technical problem. To overcome technical problems, the lecturer reported this to the program manager for improvement, while for non-technical problems, the lecturer was proactive to ask the students. Based on the results of this study, it can be concluded that the planning and implementation of listening learning in the BIPA program for academic purposes is following the principles of learning listening in a second or foreign language. However, some things need attention related to technical and non-technical problems that occur so that they can be minimized.